2016
DOI: 10.1017/rdc.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of the Soil Organic Matter Amino Acid Fraction Investigated by13C and14C Signatures of Carboxyl Carbon

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Isolating and dating individual compounds as a method to improve dating accuracy has been discussed since the 1960s in consideration of the severe difficulty associated with entirely removing extraneous carbon originating from diagenesis and other types of external contamination by conventional chemical pretreatment for radiocarbon bone dating . This isolated amino acid radiocarbon dating method has also been applied to soil . Isolating individual amino acids not only discards extraneous carbon through the separation processes, but also has the benefit of separating a bulk isotopic signal into its constituent parts.…”
Section: Relation To Other Dating Techniquesmentioning
confidence: 99%
“…Isolating and dating individual compounds as a method to improve dating accuracy has been discussed since the 1960s in consideration of the severe difficulty associated with entirely removing extraneous carbon originating from diagenesis and other types of external contamination by conventional chemical pretreatment for radiocarbon bone dating . This isolated amino acid radiocarbon dating method has also been applied to soil . Isolating individual amino acids not only discards extraneous carbon through the separation processes, but also has the benefit of separating a bulk isotopic signal into its constituent parts.…”
Section: Relation To Other Dating Techniquesmentioning
confidence: 99%
“…In addition, when high substrate concentrations are used, metabolic overload can lead to the uptake of the solute from soil but a lack of mineralization (Jones, 1999). Studies using isotopic tracers have found that at low exogenous concentrations, amino acids and peptides can be removed from soil within a matter of minutes (Ge et al, 2010;Hobbie and Hobbie, 2012;Hatté et al, 2017), which is 1-2 orders of magnitude faster than their subsequent mineralization (Fisk et al, 1998;Lipson et al, 2001;Vinolas et al, 2001). Accurately measuring substrate depletion kinetics over such short timescales therefore represents a major methodological challenge.…”
Section: Introductionmentioning
confidence: 99%